Acute Phase Proteins as Early Predictors for Immunotherapy Response in Advanced NSCLC: An Explorative Study - Schneider, Marc A.; Rozy, Adriana; Wrenger, Sabine; Christopoulos, Petros; Muley, Thomas; Thomas, Michael; Meister, Michael; Welte, Tobias; Chorostowska-Wynimko, Joanna; Janciauskiene, Sabina (Frontiers in Oncology, 2022)
In the last decade, targeting the immune system became a promising therapy in advanced lung cancer stages. However, in a clinical follow-up, patient responses to immune checkpoint inhibitors widely differ. Peripheral blood is a minimally invasive source of potential biomarkers to explain these differences. We blindly analysed serum samples from 139 patients with non-small cell lung cancer prior to anti-PD-1 or anti-PD-L1 therapies to assess whether baseline levels of albumin (ALB), alpha-1 acid glycoprotein (AGP), alpha1-antitrypsin (AAT), alpha2-macroglobulin (A2M), ceruloplasmin (CP), haptoglobin (HP), alpha1-antichymotrypsin (ACT), serum amyloid A (SAA), and high-sensitivity C-reactive protein (hs-CRP), have a predictive value for immunotherapy success. Disease progression-free survival (PFS) was calculated based on RECIST 1.1 criteria. A multivariate Cox regression analysis, including serum levels of acute phase proteins and clinical parameters, revealed that higher pre-therapeutic levels of HP and CP are independent predictors of a worse PFS. Moreover, a combined panel of HP and CP stratified patients into subgroups. We propose to test this panel as a putative biomarker for assessing success of an immunotherapy in patients with NSCLC.